Perfecting the Earth: A Piece of Possible History - C[harles] W[illiam] Wooldridge B.S., M.D. (1847-1908) (Utopia Publishing Company, 1902)
The US Army is used to revitalize the West through massive public works projects and, in doing so, creates a cooperative eutopia that spreads to the rest of the country. Gives very detailed descriptions of and plans for the specific projects, including the use of irrigation in the deserts of Southern California. See also 1898 Wooldridge.
Rpt. New York: Arno Press and The New York Times, 1971.
Keywords: Male author; US author